Comics and the World Wars - Chapman, Jane L. author. aut Link
XIV, 217 p.
Keywords: This transnational, interdisciplinary study argues for the use of comics as a primary source. In recuperating currently unknown or neglected strips the authors demonstrate that these examples, produced during the World Wars, act as an important cultural record, providing, amongst other information, a barometer for contemporary popular thinking.